Helminth infection in coldwater fishes of Suru river Ladakh, Jammu and Kashmir, India - Dar, Shabir Ahmad; Ahmed, Fayaz; Mir, M R; Dar, J A; Tak, Hidayatullah; Kuchai, J A (Recent Research in Science and Technology, 2013)
A helminthological survey of coldwater fishes of Ladakh was carried out from November 2007 to April 2009 (18 months). A total of 93 fishes belonging to two species viz., Schizothorax plagiostomus and Diptychus maculatus were collected and examined from different collection sites of Suru river, Kargil. A total of 2 helminth species viz., Neoechinorhynchus yalei Datta, 1936 and Rhabdochona himalayai Fotedar & Dhar, 1977 belonging to two helminth groups, i-e. Acanthocephala and Nematode were reported. It was found that out of 93 hosts examined, 31 were found infected with 43 parasites recovered in total, with an overall prevalence, mean intensity and abundance of 33.33%, 1.38 and 0.46 respectively. Distribution of helminth infection and its relation with sex and size of host was analysed. The helminth infection showed no significant relationship with sex of hosts however it showed mostly significant relation to size of host.